m6A Modification Prevents Formation of Endogenous Double-Stranded RNAs and Deleterious Innate Immune Responses during Hematopoietic Development - Gao, Yimeng; Vasic, Radovan; Song, Yuanbin; Teng, Rhea; Liu, Chengyang; Gbyli, Rana; Biancon, Giulia; Nelakanti, Raman; Lobben, Kirsten; Kudo, Eriko; Liu, Wei; Ardasheva, Anastasia; et al. (Immunity (Cambridge, Mass.), 2020)
N6-methyladenosine (m6A) is the most abundant RNA modification, but little is known about its role in mammalian hematopoietic development. Here, we show that conditional deletion of the m6A writer METTL3 in murine fetal liver resulted in hematopoietic failure and perinatal lethality. Loss of METTL3 and m6A activated an aberrant innate immune response, mediated by the formation of endogenous double-stranded RNAs (dsRNAs). The aberrantly formed dsRNAs were long, highly m6A modified in their native state, characterized by low folding energies, and predominantly protein coding. We identified coinciding activation of pattern recognition receptor pathways normally tasked with the detection of foreign dsRNAs. Disruption of the aberrant immune response via abrogation of downstream Mavs or Rnasel signaling partially rescued the observed hematopoietic defects in METTL3-deficient cells in vitro and in vivo. Our results suggest that m6A modification protects against endogenous dsRNA formation and a deleterious innate immune response during mammalian hematopoietic development. [Display omitted] •Loss of METTL3 inhibits proliferation and differentiation of hematopoietic stem cells•Depletion of m6A results in aberrant dsRNA formation of long m6A-modified transcripts•Loss of METTL3 induces deleterious innate immune responses in hematopoiesis•Mavs and Rnasel depletion partially rescue defects in Vav-Cre+-Mettl3fl/fl mice Little is known about the role of N6-methyladenosine (m6A) modifications in mammalian hematopoietic development. Gao et al. find that m6A modification of endogenous transcripts preserves their recognition as self by preventing aberrant formation of double-stranded RNA. Deletion of m6A writer Mettl3 and loss of m6A activates pattern recognition receptor pathways, culminating in a deleterious innate immune response and hematopoietic failure.